Vitamin D and tuberculosis: where next?. (2nd July 2018) - Brighenti, S.; Bergman, P.; Martineau, A. R.
Abstract: Tuberculosis (TB) has troubled mankind for millennia, but current treatment strategies are long and complicated and the disease remains a major global health problem. The risk of Mycobacterium tuberculosis (Mtb) infection or progression of active TB disease is elevated in individuals with vitamin D deficiency. High‐dose vitamin D was used to treat TB in the preantibiotic era, and in vitro experimental data show that vitamin D supports innate immune responses that restrict growth of Mtb. Several randomized controlled trials have tested whether adjunctive vitamin D supplementation enhances the clinical and microbiological response to standard antimicrobial chemotherapy for pulmonary TB. The effects have been modest at best, and attention is turning to the question of whether vitamin D supplementation might have a role in preventing acquisition or reactivation of latent Mtb infection. In this article, we describe the effects of vitamin D on host immune responses to Mtb in vitro and in vivo and review the results of clinical trials in the field. We also reflect on the findings of clinical trials of vitamin D supplementation for the prevention of acute respiratory tract infections, and discuss how these findings might influence the design of future trials to evaluate the role of vitamin D in the prevention and treatment of TB. Abstract : Content List ‐ Read more articles from the symposium: "The 10th International Conference on the Pathogenesis of Mycobacterial Infections".